Corporate Social Responsibility, Customer Satisfaction and Firm Performance: A Corporate Hypocrisy Perspective - Sharpe, Wen Hua; Sharma, Piyush; Leung, Tak Yan (2024)
This paper draws on recent concerns about firms potentially engaging in hypocritical (or opportunistic) behaviours through the use of corporate social responsibility (CSR), which have been referred to as greenwashing or bluewashing in the extant literature, to investigate the impact of firms’ hypocritical versus non-hypocritical (socially responsible) CSR performance on customer satisfaction. Using a sample of large US public firms from 2000 to 2018, we find a negative impact of CSR performance on customer satisfaction for hypocritical firms and a positive impact for non-hypocritical firms. These findings are consistent with the window-dressing motivations for hypocritical firms and socially responsible motivations for non-hypocritical firms. We also present a nuanced conceptual model exploring the potential impact of perceived corporate hypocrisy on both short-term and long-term financial performance through the mediating mechanism of customer satisfaction. Overall, our findings provide useful insights into the distinction between hypocritical vs. non-hypocritical CSR and the differences in their influence on firm performance through customer satisfaction. Besides extending current research into the link between CSR and firm performance and guiding future research in this area, our findings would also provide useful guidance for key stakeholders, including stock analysts, investors, managers, and policy makers. Keywords: Corporate hypocrisy, corporate social responsibility (CSR), customer satisfaction, firm performance